2020
DOI: 10.1186/s12936-020-03281-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mutations in the Plasmodium falciparum chloroquine resistance transporter, PfCRT, and association with ex vivo susceptibility to common anti-malarial drugs against African Plasmodium falciparum isolates

Abstract: Background: The Plasmodium falciparum chloroquine transporter gene (pfcrt) is known to be involved in chloroquine and amodiaquine resistance, and more particularly the mutations on the loci 72 to 76 localized within the second exon. Additionally, new mutations (T93S, H97Y, C101F, F145I, M343L, C350R and G353V) were recently shown to be associated with in vitro reduced susceptibility to piperaquine in Asian or South American P. falciparum strains. However, very few data are available on the prevalence of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 46 publications
2
14
1
Order By: Relevance
“…In this study, no mutations were detected at loci 93, 97, 101, 145, 343, 350, and 353. In an investigation of African isolates, consistent with the results of this study, no mutations at these sites were reported [ 13 ]. In this study, 5 isolates carried the mutant allele, and 3 isolates were mixed type at loci 356.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In this study, no mutations were detected at loci 93, 97, 101, 145, 343, 350, and 353. In an investigation of African isolates, consistent with the results of this study, no mutations at these sites were reported [ 13 ]. In this study, 5 isolates carried the mutant allele, and 3 isolates were mixed type at loci 356.…”
Section: Discussionsupporting
confidence: 90%
“…However, long-term use of anti-malarial drugs particularly PPQ induced ADR [ 14 ]. Previous studies indicated that several mutations of pfcrt (93 S , 97 Y , 101 F , 145 I , 343 L , 353 V , and 356 T ) were related to reducing parasite sensitivity to PPQ [ 13 , 14 , 36 39 ]. In this study, no mutations were detected at loci 93, 97, 101, 145, 343, 350, and 353.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations